A conceptual discussion on the external auditor's personality and detection of fraud - Jaffar, Nahariah; Salleh, Arfah; Mohd Iskandar, Takiah; Haron, Hasnah (Eurojournals, 2006)
The collapse of Enron has again shed some unfavourable lights on the role that external auditors play in the detection of fraud (Thomas & Clements, 2002). Inability to detect fraud may lead to a litigation action being taken against the external auditor (Palmrose, 1987). Previous research found that personality factors may be associated with job performance (Robertson, Baron, Gibbons, MacIver, & Nyfield, 2000; Barrick & Mount, 1991). Ashton (1999) suggested that certain innate personality factors can be used to predict an individual's performance, specifically the performance of auditors. This paper attempts to determine factors that may have impact on the ability of external auditors to detect the likelihood of fraud. Robertson and Callinan (1998) stated that the emergence of "Big five" factors of personality has increased the interest for researchers to examine its role. The "Big five" factors of personality are: (1) neuroticism, (2) extraversion, (3) conscientiousness, (4) openness and (5) agreeableness. This paper will specifically investigate effects of these five factors of personality on the external auditors' ability to detect the likelihood of fraud. In this paper a discussion on the development of a conceptual framework for the external auditor's personality and detection of fraud is presented.